2013
DOI: 10.1111/tpj.12345
|View full text |Cite
|
Sign up to set email alerts
|

Rye Pm8 and wheat Pm3 are orthologous genes and show evolutionary conservation of resistance function against powdery mildew

Abstract: SUMMARYThe improvement of wheat through breeding has relied strongly on the use of genetic material from related wild and domesticated grass species. The 1RS chromosome arm from rye was introgressed into wheat and crossed into many wheat lines, as it improves yield and fungal disease resistance. Pm8 is a powdery mildew resistance gene on 1RS which, after widespread agricultural cultivation, is now widely overcome by adapted mildew races. Here we show by homology-based cloning and subsequent physical and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
163
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(171 citation statements)
references
References 85 publications
1
163
0
2
Order By: Relevance
“…RT-qPCR primers and master mixes used for the targets ZmWAK-RLK1.1 and ZmWAK-RLK1.2 and the reference gene FPGS are described in SI Appendix, Table S8 (5 s for FPGS). Specificities of amplicons, RT-minus control check, and efficiency calculation were performed as described in Hurni et al (38). To allow comparison of the expression levels between the two splice variants ZmWAK-RLK1.1 and ZmWAK-RLK1.2, the RT-qPCR data were calibrated on the basis of plasmid DNA containing the ZmWAK-RLK1.1 or ZmWAK-RLK1.2 construct, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RT-qPCR primers and master mixes used for the targets ZmWAK-RLK1.1 and ZmWAK-RLK1.2 and the reference gene FPGS are described in SI Appendix, Table S8 (5 s for FPGS). Specificities of amplicons, RT-minus control check, and efficiency calculation were performed as described in Hurni et al (38). To allow comparison of the expression levels between the two splice variants ZmWAK-RLK1.1 and ZmWAK-RLK1.2, the RT-qPCR data were calibrated on the basis of plasmid DNA containing the ZmWAK-RLK1.1 or ZmWAK-RLK1.2 construct, respectively.…”
mentioning
confidence: 99%
“…Expression of ZmWAK-RLK1 was quantified in a reverse transcription, quantitative real-time PCR (RT-qPCR) assay, using a CFX96 Real-Time System C1000TM Thermal cycler (Bio- (38), and first-strand cDNA was synthesized from 0.5 Îźg RNA, using 1/2 reaction of the iScript Advanced cDNA Kit (172-5038, Bio-Rad). RT-qPCR primers and master mixes used for the targets ZmWAK-RLK1.1 and ZmWAK-RLK1.2 and the reference gene FPGS are described in SI Appendix, Table S8 (5 s for FPGS).…”
mentioning
confidence: 99%
“…We have found that the Pm8 gene derived from rye and present on the frequently used 1RS/1BL translocation in wheat is an ortholog of the wheat Pm3 resistance gene (Hurni et al 2013 ). The fi nding that orthologous genes have maintained their function against the mildew pathogen over an estimated seven million years revealed a surprising evolutionary stability of powdery mildew resistance gene activity.…”
Section: Natural Diversity As a Rich Resource For Basic And Applied Wmentioning
confidence: 99%
“…Nearly 70 Pm-resistance genes/alleles have been identified in wheat's germplasm, and many of them have been successfully used in breeding programs. However, only three of these genes have been cloned: Pm3, Pm8, and Pm21 (Yahiaoui et al, 2004;Cao et al, 2011;Hurni et al, 2013). Pm3 is located on the short arm of wheat's chromosome 1A and encodes a coiled-coil nucleotide-binding site leucine-rich repeat (CC-NBS-LRR)-resistance protein.…”
Section: Introductionmentioning
confidence: 99%
“…Pm3 is located on the short arm of wheat's chromosome 1A and encodes a coiled-coil nucleotide-binding site leucine-rich repeat (CC-NBS-LRR)-resistance protein. Pm8 was mapped to the short arm of rye's chromosome 1R, and cloned using a homology-based approach (Hurni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%